Coming Together: A Case Study of Collaboration Between Student Affairs and Faculty at Norfolk State University - Commodore, Felecia; Gasman, Marybeth; Conrad, Clifton; Nguyen, Thai-Huy (Frontiers in Education, 2018)
Using an open-ended, case study approach, we sought to examine academic and student affairs models of success at a historically Black university. Our findings address the ways in which coordination and collaboration—between academic affairs and student affairs—aid in fostering students success, retention, and degree attainment. Our findings are particularly relevant for under-resourced environments and we argue that bringing the administrative functions of academic affairs and students affairs together provides a greater understanding among faculty and staff, and engenders a more nurturing and supportive environment for students. Our research is situated within the larger areas of higher education and student affairs-focused research.